AB0071 Dual role of autophagy in stress-induced cell death in rheumatoid arthritis synovial fibroblasts. (23rd January 2014) - Kato, M.; Ospelt, C.; Michel, B. A.; Gay, R. E.; Gay, S.; Klein, K.
Abstract : Background: Autophagy is a highly regulated process activated by various cellular stress conditions that removes damaged and misfolded proteins from cells in the regulation of cell death. The autophagy-linked FYVE protein (ALFY), one of the autophagy adaptors, was shown to facilitate the autophagic degradation of p62, an ubiquitin binding protein. Recently, autophagy was shown to be increased in rheumatoid arthritis (RA) (Lin et al., ARD 2012). Objectives: To investigate the activation of autophagy after the induction of poly-ubiquitinated protein accumulation in rheumatoid arthritis synovial fibroblasts (RASF) and the role of this pathway in the regulation of cell death. Methods: To induce the accumulation of poly-ubiquitinated proteins, RASF and osteoarthritis synovial fibroblasts (OASF) were treated with Thapsigargin (TG, 5µM), an inducer of endoplasmic reticulum (ER) stress, and MG132 (50µM), a proteasome inhibitor, for 24, 48, 72, 96, 120 and 144h. 3-methyladenine (3-MA, 5 mM) was used as an autophagy inhibitor. The amounts and distribution of poly-ubiquitinated proteins and p62 were evaluated by immunoblotting and immunofluorescence microscopy. Autophagy activation was monitored by immunoblotting using antibodies against LC3. OASF were transfected with siRNA targeting ALFY. Cell death was evaluated by flow cytometry using annexin V/ propidium iodide staining and a caspase-3 activity assay (NucView 488, Biotium). Results: In RASF, the induction of autophagy by TG or MG132 was increased compared to OASF. While cell death induced by TG was increased in RASF compared to OASF (p=0.01, n=3), RASF were more resistant to MG132-induced cell death than OASF (p=0.03, n=4). However, apoptosis as measured by caspase-3 activity was strongly induced by MG132 but only to a minor extent by TG. Treatment of RASF with 3-MA almost completely blocked cell death induced by TG and the induction of caspase-3, whereas it induced apoptosis after proteasome inhibition. ER stress induced a strong accumulation of p62-positive poly-ubiquitinated protein aggregates accompanied by the formation of large vacuoles in RASF but not in OASF, while the total amount of TG-induced poly-ubiquitinated proteins was similar in RASF and OASF. Furthermore, TG-induced p62 protein expression was increased in RASF compared to OASF (p=0.04, n=4). On the other hand, TG-induced ALFY expression was reduced in RASF compared to OASF, and ALFY knockdown promoted the accumulation of p62, the formation of poly-ubiquitinated protein aggregates and cell death. Conclusions: Our data provide the first evidence on a dual role of autophagy in the regulation of cell death in RASF. Whereas autophagy promotes cell death induced by ER stress, it has a protective role in apoptosis induced by proteasome inhibition. An imbalance in the expression of p62 and ALFY plays a critical role in the formation of poly-ubiquitinated protein aggregates under ER stress conditions in RASF and promotes cell death. References: Lin et al., ARD 2012 Acknowledgements: Japan Rheumatism Foundation, IAR, IMI-BTCure Disclosure of Interest: M. Kato Grant/research support from: Japan Rheumatism Foundation, C. Ospelt Grant/research support from: IAR, IMI-BTCure, B. Michel: None Declared, R. Gay Grant/research support from: IAR, IMI-BTCure, S. Gay: None Declared, K. Klein Grant/research support from: IAR, IMI-BTCure